Bus superstructure rollover analysis using finite element method - Rahman, Mahathir (2017)
Bus rollover accidents cause severe damage to its superstructure which results in severe injury and death to the passengers. The bus superstructure must be strong enough to absorb energy of impact at a time the superstructure touches the ground. In this work, a bus superstructure with a capacity of forty four passengers was analysed to identify the capability of the superstructure to absorb crash energy using two different materials and varying structure thicknesses during a bus rollover crash. The superstructure was modelled and simulated according to the United Nation Economic Commission of Europe Regulation Number 66 (UN-ECE, R66) using the finite element analysis software, LS - DYNA. The simulation was conducted to determine the permanent deformation of the superstructure of the bus un-laden and laden kerb weight on the passenger residual space during the rollover crash, and the effect of 3.0 mm, 2.3 mm, and 1.6 mm thicknesses of Ultra-galvanise (Ultragal) C350 and 2.3 mm thickness of material made with ASTM A500 grade B on the deformation. The validation process was completed using the quasi-static three-point bending simulation on the waist rail knot of the bus superstructure. The simulation results clearly indicate that appropriate material selection is critical to design and build a strong and lightweight bus superstructure. The simulation of both laden and un-laden kerb weight scenario significantly shows that a heavy frame design will affect the overall bus superstructure, especially the standard hoop structure. The thickness and the type of material assigned to the standard hoop structure also need to be considered to prevent the structure from collapsing and intruding the passenger residual space during a rollover crash. In this study, for bus standard hoop structure with Ultragal C350 material, the intrusion reducing linearly with increasing thickness over the thickness range of 1.6 mm to 3 mm. From the results obtained, the value of thickness for zero intrusion is found to be 2.75 mm. For laden bus structure simulation zero intrusion obtained is 3.1 mm by extrapolation method. The simulation result for the un-laden kerb weight scenario shows that the standard hoop structures does not intrude the passenger residual space where there is a distance of 53 mm between the standard hoop structure and passenger residual space. The un-laden kerb weight scenario shows that the structure absorbed a maximum internal energy of 95 MJ while the laden kerb weight scenario shows that with the same standard hoop structures thickness had intrude 99 mm into the passenger residual space with higher energy absorbed (internal energy) by the structure at 137 MJ.